Concurrent Momentum and Contrarian Strategies: Evidence from Indonesia - Rafik, Abdur; Marizka, Syifa Primaratri (The Indonesian Capital Market Review, 2017)
This study aims to test the relative performance of contrarian and momentum strategies for the middle-term and long-term horizons in the Indonesian capital market. The test is performed to constituents of Kompas100 Index during 2009-2014. The results reveal that the superior performance of the momentum in the intermediate term is sensitive to the formation horizons. In the long term (after 24 months), however, the contrarian is more profitable than momentum. It is also found that there is no relationship between the generated returns and the value and the size premiums like the findings of many studies regarding the long-run return anomalies in developed countries.